Effect of toxin A and B of Clostridium difficile on rabbit ileum and colon. Issue 1 (January 1986) - Mitchell, T J; Ketley, J M; Haslam, S C; Stephen, J; Burdon, D W; Candy, D C; Daniel, R
Abstract : The effect of purified toxin A and partially purified toxin B on rabbit ileum and colon was investigated. Toxin A caused tissue damage which was followed by permeability changes and fluid accumulation in both tissues. Toxin A did not increase the permeability of the colon to the extent observed for ileum; secreted fluid contained less protein of plasma origin. Toxin B had no effect on either tissue. Secretory and tissue damaging properties of crude C difficile toxins were found to be due to toxin A.